THE INCIDENCE AND CLINICAL CORRELATION OF DACRYOCYSTITIS WITH NASAL PATHOLOGY IN A TERTIARY CARE HOSPITAL. - Muhammad Imran Shah,; Zara Sajid,; Bushra Aaqil,; Hasan Sajid Kazmi,; Tahira Sajid,; Usman Ameen, (Journal of Ayub Medical College Abbottabad, 2026)
Dacryocystitis is an inflammation or infection of the lacrimal sac. This condition frequently occurs secondary to the nasolacrimal duct blockage, causing tear stasis and ultimately infection. Objective: To identify the relationship between chronic dacryocystitis and different nasal pathologies for accurate diagnosis, management, and preventing relapse in a cohort of 320 patients. Methods: This descriptive cross-sectional study was conducted at the ENT and Eye Departments of Ayub Teaching Hospital, Abbottabad from 1st April 2024 to 31st January 2025. The study enrolled 320 patients of age 18 years and above, irrespective of gender with clinically and or radiologically diagnosed Dacryocystitis. Collected data was analyzed to determine the prevalence of nasal pathologies. Data analysis was done using SPSS version 28.Results: The study highlights that 32.8% cases of chronic dacryocystitis had underlying nasal pathologies with deviated nasal septum in 15%, hypertrophied inferior turbinate 6.9%, nasal polyps 5.9%, rhinolithiasis 1.6 %, nasal tumors 3.4% and no pathology was found in 67.2% of cases. Conclusion: This study demonstrates an important correlation between chronic dacryocystitis and nasal abnormalities and thus highlights the importance of interdisciplinary strategy for the diagnosis and management of chronic dacryocystitis.